2022
DOI: 10.3389/fonc.2022.994726
|View full text |Cite
|
Sign up to set email alerts
|

Nimotuzumab combined with chemoradiotherapy for the treatment of cervical cancer: A meta-analysis of randomized controlled trials

Abstract: ObjectivesTo assess the clinical efficacy and toxicity of nimotuzumab in combination with chemoradiotherapy or chemoradiotherapy alone in the treatment of cervical cancer.MethodsThe PubMed, Embase, Cochrane Library, Web of Science, China National Knowledge Infrastructure, China Biomedical Medicine, Wanfang, and VIP databases were systematically searched for relevant literature. Ultimately, six randomised controlled trials (n=393) were included in our meta-analysis.ResultsA total of 393 patients were included, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…It has been approved by many countries for the treatment of nasopharyngeal carcinoma, pediatric and adult glioma, and advanced esophageal cancer, etc. ( 2 , 12 , 13 ). Since 2009, several studies have reported that nimotuzumab combined with RT/CRT is used for the treatment of LA-SCCHN.…”
Section: Introductionmentioning
confidence: 99%
“…It has been approved by many countries for the treatment of nasopharyngeal carcinoma, pediatric and adult glioma, and advanced esophageal cancer, etc. ( 2 , 12 , 13 ). Since 2009, several studies have reported that nimotuzumab combined with RT/CRT is used for the treatment of LA-SCCHN.…”
Section: Introductionmentioning
confidence: 99%